The impact of coblation and non-coblation techniques on hemorrhage and pain outcomes in tonsillectomy: A meta-analysis - Kuncahyo, Sandi Dwi; Putra, Mega Memory Rahasa; Istyawati, Ersty (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Tonsillectomy, a common surgical procedure, carries significant complications, including haemorrhage and postoperative pain, impacting patient morbidity and mortality. This study explores the effectiveness of coblation compared to traditional non-coblation techniques in managing these complications. Coblation, proposed to reduce risks associated with tissue removal, was evaluated through a systematic literature search using databases such as PubMed, Google Scholar, and Cochrane. The selected studies were rigorously analysed based on specific inclusion and exclusion criteria. Results from ten journals included in this review indicate no significant difference in primary haemorrhage outcomes between coblation and non-coblation techniques (odds ratio 1.49; 95% CI: 0.68-3.23; p=0.32), with low heterogeneity (I²=0%; p=0.81). However, coblation was associated with a statistically significant reduction in secondary haemorrhage (odds ratio 0.66; 95% CI: 0.45-0.95; p=0.03) and postoperative pain (effect size -0.84; 95% CI: -0.94 to -0.74; p < 0.00001). These findings suggest that coblation may be more effective in reducing secondary haemorrhage and postoperative pain compared to non-coblation techniques.